Differences in Knowledges about Nutritions Status before and after being Given Health Education using Leaflet for Toddler Mother - Meirna Eka Fitriasnani; Galuh Pradian Yanuaringsih; Yunita Lamunde (Journal of Global Research in Public Health, 2021)
Nutritional Status is a body condition caused by a balance between nutrient intake and need. Toddler Nutrition Status is a condition of child's health determined by the degree of physical needs of energy and nutritional substances. Based on the initial survey of research in the village corner of Kadiri in March was obtained the results that from 10 mothers of toddlers obtained 60% of infants have not understood the status of nutrition and 40% of mothers are already familiar with nutrition status. Factors affecting the nutritional status of the toddler mother is a factor in the knowledge of nutritional status in the village corner of the working Rw 2 area of ​​Sukorame Kadiri City clinic year 2020. This research is comparative analytical research. The population of 41 children is in the corner of Kadiri. Randomized sampling technique with simple random sampling of 35 respondents. The statistical test used was the Wilcoxon test. This study was conducted in 35 respondents with the results of knowledge prior to the most knowledgeable majority health education almost all (74.3%) Respondents and after a good knowledgeable majority health education (60.0%), Wilcoxon test Results stated P value < A < 0.000 < 0.05 which means there is an increase in knowledge before and after the counseling of nutritional status in a toddler's mother. The conclusion that nutrition status health education in toddler mothers managed to increase knowledge and achievement for health care institutions and health achievement in the society.